Berberine isolated from Mahonia nepalensis as an eco-friendly and thermally stable corrosion inhibitor for mild steel in acid medium - Nabin Karki (Elsevier, 2021)
Background: The environmental and economic benefits have been the driving force in search of efficient corrosion inhibitors for iron/steel used in industrial acidic medium. This study reports on berberine isolated from methanol extract of high-altitude (1347 m) shrub Mahonia nepalensis as a highly efficient and thermally stable corrosion inhibitor for mild steel (MS) in 1.0 M H2SO4 simulating acid pickling condition. Methods: The weight-loss and electrochemical methods revealed the fast adsorption of berberine.Significant Findings: It achieved above 91% inhibition efficiency (IE) in 0.25 h and reached 94% in 6 h for 1000 ppm berberine. The IE increased with concentration and temperature, giving an IE of 97.2% at 328 K, which makes it a promising candidate for industrial application. It behaved as a mixed type of inhibitor as revealed by open circuit potential and polarization curves. The results indicated suppression of the corrosion by effectively forming an adsorbed berberine layer on the MS surface. Adsorption of the berberine followed a Langmuir adsorption isotherm. The thermodynamic parameters such as activation energy (43.19 kJ/mol), free energy (−35.05 kJ/mol), enthalpy (40.55 kJ/mol), and entropy (−97.83 J/molK) of adsorption supported both physical and chemical interactions of berberine with MS surface. The obtained results also revealed that the adsorption process was endothermic and spontaneous in nature.